WHAT IS BEHAVIORAL FINANCE?? - Kamelia Agustini; Senny Luckyardi; Nugraha; Maya Sari (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Behavioral Finance is the science of behavioral, psychological aspects for investors in making investment decisions. Behavioral Finance explains deviation/bias with psychological terminology. Over the past forty years, traditional finance has been the dominant theory in the academic community. However, scholars and investment professionals are beginning to investigate an alternative theory of finance known as behavioral finance. Behavioral finance seeks to explain and increase public awareness of the emotional factors and psychological processes of individuals and entities investing in financial markets. Behavioral finance is evolving and an appreciation for this interdisciplinary research is the underlying foundation of this emerging discipline. There are four general principles of Behavioral Finance, namely Overconfidence, Financial Cognitive Dissonance, Theory of Regret and Prospect Theory.